Advances in ophthalmic preparation: the role of drug nanocrystals and lipid-based nanosystems. (15th March 2020) - Peters, Maria Christina Camasmie; Santos Neto, Edson dos; Monteiro, Lis Marie; Yukuyama, Megumi Nishitani; Machado, Marcella Gabrielle Mendes; de Oliveira, Isabela Fernandes; Zanin, Maria Helena Ambrosio; Löbenberg, Raimar; Bou-Chacra, Nádia
Abstract: Nanocrystals and lipid-based nanosystems have the potential to play a crucial role in a significant shift in the treatment of ophthalmic diseases. These drug delivery systems allow overcoming the barriers imposed by anatomy and physiology of the organ of vision. This review aims to present new perspectives for these innovative preparations, emphasising the applications of the nanocrystal and lipid-based nanosystem while outlining their advantages and the drawbacks. The in vivo performance of the lipid-based nanosystems was highlighted. Lipid-based nanosystems and nanocrystals showed a prolonged effect, improved ocular bioavailability, upper therapeutic efficacy, higher permeation, prolonged residence time, and sustained drug release, compared to the current applications. Well-established and innovative developments updates of these systems are highlighted herein.